2015
DOI: 10.1063/1.4917042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inherent structure shear stress of supercooled liquids on their shear moduli

Abstract: Configurations of supercooled liquids residing in their local potential minimum (i.e. in their inherent structure, IS) were found to support a non-zero shear stress. This IS stress was attributed to the constraint to the energy minimization imposed by boundary conditions, which keep size and shape of the simulation cell fixed. In this paper we further investigate the influence of these boundary conditions on the IS stress. We investigate its importance for the computation of the low frequency shear modulus of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…For this reason the normalization in Eqs. (12) and (13) is to the number of particles in the system. Of course, definitions (5), (6) and (12), (13) should lead to exactly the same result, i.e., to the value of the macroscopic stress tensor.…”
Section: The Green-kubo Expression For Viscosity and Microscopic mentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason the normalization in Eqs. (12) and (13) is to the number of particles in the system. Of course, definitions (5), (6) and (12), (13) should lead to exactly the same result, i.e., to the value of the macroscopic stress tensor.…”
Section: The Green-kubo Expression For Viscosity and Microscopic mentioning
confidence: 99%
“…Any physically meaningful structural CFs describing isotropic states should not depend on the orientation of the observation coordinate frame. This means that (time or Gibbs-ensemble averaged) CFs (5,6,7) and (12,13,14) should be the same in any observation coordinate frame. Therefore, we may think that the averaging over t o also includes in itself the averaging over all possible orientations of the observation coordinate frame.…”
Section: The Green-kubo Expression For Viscosity and Microscopic mentioning
confidence: 99%
See 2 more Smart Citations
“…In several recent publications it has been discussed that the inherent structures of the model liquids have non-zero macroscopic stress states [4][5][6]. It has been demonstrated that these non-zero stress states are related to the boundary conditions which put constraints on the allowable configurational states of the systems [5]. Given of the Maxwell model discussed above, it is natural to assume that the non-zero macroscopic stresses of the inherent states manifest about the potential energy elastically stored in the inherent states.…”
Section: Introductionmentioning
confidence: 99%